PENGARUH DANA TRANSFER KE DESA TERHADAP JUMLAH PENDUDUK MISKIN PERDESAAN DI JAWA TENGAH:ANALISIS SEBELUM DAN SESUDAH PANDEMI COVID-19 TAHUN (2018-2022) - Prasistiasari, Lutfinar; Isnowati, Sri (Fakultas Ekonomi dan Bisnis Universitas Pekalongan, 2025)
Poverty is a low standard of living, namely the existence of a level of material deprivation in a number or group of people compared to the general standard of living that applies in the community concerned. This research seeks to assess the effects of village transfer funds on the number of rural poor people in Central Java: a comparative analysis before and after the Covid-19 Pandemic in 2018-2022. This study employs a quantitative mothodology that emphasizes the analysis of numerical data processed using statistical methods. This research approach is more aimed at knowing and measuring the influence and relationship of village fund variables, village fund allocations and financial assistance to village governments before and after the Covid-19 Pandemic (2018-2022) on the number of poor rural residents in Central Java Province. The results of the study show that the village fund variables and village government financial assistance have a negative and significant effect on the number of poor people in the Regency of Central Java Province. In addition, the village fund allocation variable is negative and has nosubstantial effect on the number of people living in poverty in the Regency/City of Central Java Province.